Land suitability evaluation for changing spatial organization in Urmia County towards conservation of Urmia Lake. (April 2017) - Nouri, Hedayat; Mason, Robert J.; Moradi, Nosrat
Abstract: One of the most effective ways to reverse the decline of Iran's iconic Urmia Lake is to directly confront the development patterns that have contributed to the current crisis. This study's objective is to create a model for conservation of Urmia Lake that identifies suitable lands for agricultural and residential development in Urmia County that are distant from Urmia Lake. This was accomplished through a Geographic Information System-based multi-stage process. The first step involved production of maps based on an initial assessment of the region's geography, geomorphology, landforms, and hazards potential. In the next step, all of the parameters were overlaid and land suitability maps were generated by using determinant maps. In developing the final map, the lands were divided into four classes for future development potential: highly suitable, suitable, marginally suitable and not suitable. The results showed that well away from highly populated regions adjacent to Urmia Lake, there are highly suitable and suitable lands that presently contain 14 and 8 percent of total settlements, respectively. The highly suitable and suitable lands, which cover 5.6 and 6.7% of the total area, may serve as appropriate axes for changing the traditional spatial organization of the region, redirecting future development and consequently decreasing ecological pressure on lands close to Urmia Lake as well as preventing further excessive usage of water resources in the region. Highlights: Developing a model for reconfiguring the spatial organization of Urmia County. The train significantly impacts a majority of the land use potential. There are suitable lands for future development in the western part of Urmia County. The reconfigured spatial organization can decrease ecological pressure on Urmia Lake.